Influence of thermoplastic interleaves and its healing effect on the failure mechanisms of open-hole notched composite laminates - Zhang, Tianqi; Yasaee, Mehdi (Elsevier, 2022)
This paper has explored the effect of thermoplastic interleaves on the mechanical performance of open-hole notched Carbon Fibre Reinforced Polymer (CFRP) composites. A fully verified FE model was produced to replicate the experimental results, as well as to study the sensitivity of the interlaminar properties on the open hole tensile failure mechanism sequence. Both experimental and numerical analysis results show that, the failure mechanisms and sequences are closely linked to the interfacial toughness, strength, and stiffness. With the addition of thermoplastic interleaves, the higher interfacial fracture toughness allows for a stable and gradual delamination growth. This effect lowered the interfacial strength, thereby releasing stress concentrations at the open-hole site. These features result in the higher overall load carrying capacity. A healing treatment on the thermoplastic interleaves post drill operation was conducted and assessed their effectiveness to fix the drill-induced damage through detailed microscopy inspections, to understand the condition of specimens’ interfaces before and after the healing treatment. In comparison to non-healing treated interleaved sample, the healing treatment increased the tensile strength of the sample with the failure sequence changed.
Keywords: Carbon fibres; Delamination; Fracture toughness; Interfacial strength; Finite element analysis (FEA)